Point of Care (POC) Influenza Immunization for Pregnant Women, Calgary Zone, Alberta Health Services - Manji, Sofiya; McDonald, Sheila; Metcalfe, Amy; Nerenberg, Kara; Zhang, Jing; Castillo, Eliana (International Journal of Population Data Science, 2018)
Introduction Vaccinating pregnant patients for neonatal protection needs to be integrated into prenatal care as new vaccines emerge. Uptake of influenza vaccine, universally recommended in pregnancy, is low. Immunization was offered and administered to pregnant women at point of care (POC) during two flu seasons at an urban tertiary care center. Objectives and Approach Primary objective is to determine if POC impacts immunization rate during flu season among a cohort of pregnant women by location and gestational age. Secondary objectives are to examine the pattern of influenza-like illnesses (ILI) among vaccinated and unvaccinated women, and to describe pilot outcomes of POC. Four consecutive influenza seasons (2014/2015, 2015/2016, 2016/2017, 2017/2018) will be examined using seven databases: a) Clinibase, b) National Ambulatory Care Reporting System; C) Discharge Abstract Database; d) Physician Claims; e) Alberta Perinatal Health Program; f) Calgary Zone Public Health; and g) Pharmaceutical Information Network. Outcomes will be examined descriptively using frequencies and proportions. Results Based on the preliminary analysis, approximately 10, 000 visits among 2,500 women occurred during each flu season at the four obstetric care locations: two outpatient clinics and two inpatient units. The proportion of pregnant women who received the flu vaccine ranged from 15-21% during the first three flu seasons. Majority of the women received the vaccine at the flu campaigns (range 48-67%), followed by pharmacy (20-32%). For the 2017-2018 season, year to date uptake rates in outpatient clinics are significantly higher. Final results on additional outcomes will be available by September 2018. Conclusion/Implications In completing this study, we hope to better understand the patterns of immunization uptake in pregnancy by place of immunization and gestational age, i.e. identifying optimal “window of opportunity”. Results will inform the infrastructure needed to collect data on vaccines administered during pregnancy and linkage to maternal and infant outcomes.